(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The article is devoted to developing and evaluating the effectiveness of interdisciplinary educational modules of the Russian language for students of non-philological specialties. The study is based on the hypothesis that integrating the Russian language into professional disciplines contributes to deeper and more functional language acquisition and improves students’ professional competencies. The paper presents methodological approaches to creating educational modules that combine language learning with relevant topics and tasks specific to the chosen profession. Performance criteria are described, including qualitative and quantitative indicators, such as mastering professional vocabulary, improving communication skills in professional contexts and increasing student motivation. The authors analyze the results of the pilot application of the developed modules in several higher educational institutions, assessing their impact on students’ educational process and professional development. The article also contains recommendations on adapting modules for various specialties and offers methods for evaluating their effectiveness in dynamics. The study demonstrates how an interdisciplinary approach can enrich the educational process and contribute to a deeper integration of the Russian language into specialized education